Enhancing qur’anic education among children: an analysis of al-Qabisy’s book - Md Sawari, Siti Salwa; Awang Mat, Muhamad Zahiri; Mustapha, Nurul Izzah (Edusage Network, 2018)
The importance of Qur’anic teaching emphasized clearly in Islam, yet there are still many children who are left behind in term of their Qur’anic reading and understanding. Therefore, it is important to explore the previous experiences way in enhancing the Quranic education which later on can improve children understanding towards The Quran. This study intends to provide an analysis of al-Qabisy’s ideas based on his book. Specifically, the purpose of this study is to explore Al-Qabisy’s main ideas in Qur’anic education, and the implications of his ideas on enhancing Qur’anic teaching among children. This study used content analysis method to ascertain all research objectives. As a result, this study discovers eight main components of teaching the Quran; learner level, educators, intention, educator’s responsibility, syllabus, schedule, learning stages, and assessment. The entire component presented in this book, are significantly beneficial in enhancing Qur’anic teaching among children. It is hoped that the ideas presented in this article will be helpful in upgrading the levels of Qur’anic teaching among children.